2017
DOI: 10.1111/irv.12504
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for serious outcomes associated with influenza illness in high‐ versus low‐ and middle‐income countries: Systematic literature review and meta‐analysis

Abstract: AimTo determine factors associated with a serious outcome (hospital admission or severe outcome: critical care or death) and associated with illness caused by laboratory‐confirmed influenza, with a specific interest in low‐ and middle‐income countries (LMIC).MethodDatabases were searched on 11 March 2016 for reports of influenza and factors associated with mortality or morbidity in humans, with no language restrictions. Pooled risks were estimated using random‐effects models.ResultsDespite the heterogeneity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 42 publications
5
105
2
2
Order By: Relevance
“…Early administration of NAI therapy is associated with better outcomes in severe influenza [40,41]. Old age, obesity, pregnancy and chronic medical conditions, such as COPD, diabetes mellitus, and chronic kidney disease, have been associated with poorer outcomes in patients with influenza [35,42,43]. However, in our study only cardiovascular disease was identified as a risk factor for mortality in FluA-p patients.…”
Section: Discussionmentioning
confidence: 50%
“…Early administration of NAI therapy is associated with better outcomes in severe influenza [40,41]. Old age, obesity, pregnancy and chronic medical conditions, such as COPD, diabetes mellitus, and chronic kidney disease, have been associated with poorer outcomes in patients with influenza [35,42,43]. However, in our study only cardiovascular disease was identified as a risk factor for mortality in FluA-p patients.…”
Section: Discussionmentioning
confidence: 50%
“…Several papers have showed an association between influenza infection and myocardial infarction, chronic obstructive pulmonary disease exacerbations and diabetic crises [18,23,24,27,48,49]. This also means that at least half of the study population were probably at higher risk for severe influenza disease and outcome including death [50].…”
Section: Discussionmentioning
confidence: 98%
“…Another study assessed risk factors for poor outcomes in patients with influenza and found that pregnant women, patients with HIV, children under 5 years old, and children with neurologic disorders who live in low-and middle-income countries experience worse outcomes than those who live in high-income countries. 17 Nonetheless, the authors also reported that poor outcomes in patients with comorbidities were observed in both high-and lowresource settings. Field et al 18 published an updated guideline on cough due to tuberculosis.…”
Section: Discussionmentioning
confidence: 99%